A Content Analysis of Argumentative Structure in Pre-Service Teachers’ Writing - Nurul Nurfitriana; Nur Arifah Drajati; Hefy Sulistyawati (EDULANGUE, 2019)
This study aims to describe the argumentative structure in pre-service teachers’ writing. The model argument structure was based on the adapted Toulmin (1958, 2003) consisting of six elements (i.e., claim, data, counter-argument claim, counter-argument data, rebuttal claim, and rebuttal data). The objects of this study are the writings of the fifth semester pre-service teachers' who, at that moment, were joining an academic writing course. The findings revealed that data dominated the constituent of argumentative structure based on adapted Toulmin’s model, then followed by a claim in the second place. The other structure was also found; however, it moderately in a small amount. The position and the relevancy of the papers were varied. As the implication, this study used as a model of scaffolding for pre-service teachers for giving basic knowledge of writing argumentative writing for students, so they have good skills in argumentation writing